PENDAMPINGAN UMKM KRIPIK PISANG ROLINA PEMATANG SIJONAM MELALUI QRIS DAN KONTEN MARKETING - Anhar Nasution, Mhd Khairul; Syifa Priatna, Nur Asy; Pratma, M. Aldi; Ramadhan, M. Bintang; Harahap, Aninda Muliani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The era of the Industrial Revolution 4.0 has accelerated digital transformation, including in payment systems, which are now an important strategy to support the strengthening of the national financial system. One of the innovations developed is QRIS as a applicative, secure, and efficient cashless payment solution for UMKM and consumers. This community service activity was carried out by UINSU KKN students in Pematang Sijonam Village with a focus on assisting the digitization of Keripik Pisang Rolina MSMEs through the implementation of QRIS. The implementation methods included preparation and socialization, registration and activation of QRIS accounts through the GoPay Merchant application, delivery and installation of QRIS codes, product brochure creation, logo design, and simple marketing content creation. The results of the activity show that the use of QRIS provides tangible benefits in the form of ease of transactions, financial management efficiency, improved professional image, and expanded market access. This program is expected to be the first step in strengthening the competitiveness of MSMEs in the digital era.